Determination of fungi and some heavy metals in locally cheeses - Noaman, Amir Ahmed; Al- Azzawi, Muhammed N. Ali (Iraqi Journal of Science, 2022)
In this study four cheese samples were randomly collected from local markets. These cheese samples were Ishaqi, Danone, Arab white cheese and Agricultural college cheese.Results obtained revealed that all these cheese samples were contaminated by fungi in addition to the presence of same heavy metals under study which were Fe, Pb, Ni and Cr. All fungal contaminat were identified which were contaminated them in winter (January). However, fungal pollution in summer was 100% while in winter was 50% Aspergillus niger was polluted chees samples100% in summer while it was 75% in winter. Aspergillus fumigatus was polled cheese samples under study 50% in summer and 0% in winter .Results for heavy metals determination revealed that Fe was contaminated cheese samples followed by Ni, Pb and finally Cr and the percentage of their presence was (0.24, 0.006, 0.006, 0.001 ppm) respectively .